Design, synthesis, biological assessments and computational studies of 3-substituted phenyl quinazolinone derivatives as promising anti-cancer agents - Maryam Moghtader Mansouri; Leila Emami; Zahra Rezaei; Soghra Khabnadideh (BMC Chemistry)
Abstract A new series of 3-substituted phenyl quinazolinone derivatives were designed and synthesized as anti-cancer agents. The most potent derivative with IC50 values of 12.84 ± 0.84 and 10.90 ± 0.84 µM against MCF-7 and SW480 cell lines was comparable to Cisplatin and Erlotinib as positive controls. Cell cycle analysis showed that the most active compound could arrest at S phase in MCF-7 breast cancer cells. The apoptosis assay demonstrated the induction of apoptosis in the MCF-7 cell line, too. Molecular docking results showed better accommodation of the most active compound through hydrogen bonding interaction in the binding site of EGFR enzyme. Molecular dynamics simulations for the potent analogue demonstrated well binding stability compared to the less active analogue, with a lower RMSD, Rg and more interactions with the original active site residues. DFT calculations were performed on the active and inactive compounds, using Gaussian 09 at the M06-2X/6–31 + G(d) theoretical level. ADME (Absorption, Distribution, Metabolism, and Excretion) properties showed that most of the compounds are in acceptable range of Lipiniski rule. These findings underscore the potential of the synthesized compounds as potent cytotoxic inhibitors and provide insights for developing effective treatments for cancer therapy.